ANALISIS STRATEGI GURU DALAM MENSTIMULASI KEMAMPUAN KOGNITIF ANAK USIA 5 - 6 TAHUN DI TK KASIH BAPA PERCUT - Semadi Warni Hia; Gita Noveri Eza (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze teacher strategies for stimulating the cognitive abilities of 5-6-year-old children at Kasih Bapa Percut Kindergarten. The background of this study is based on initial observations, which indicate that children's cognitive abilities have developed according to their developmental stages, as evidenced by their ability to group, recognize concepts, and respond to teacher questions. This study used a descriptive qualitative approach. The subjects consisted of two classroom teachers and 5-6-year-old children. Data collection techniques included observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that teacher strategies for stimulating children's cognitive abilities encompass preparation, implementation, evaluation, and follow-up. During the implementation phase, teachers used question-and-answer strategies, hands-on practice, learning media, and play activities that actively engaged children. Teachers also provided motivation and reinforcement, and conducted evaluations through reflection and question-and-answer sessions. Follow-up was carried out through continued guidance and collaboration with parents.